Hepatitis C infection is associated with hepatic toxicity but does not compromise the survival of patients with diffuse large B cell lymphoma treated with rituximab-based chemotherapy. Issue 2 (February 2015) - Chen, Tzu-Ting; Chiu, Chang-Fang; Yang, Tse-Yen; Lin, Ching-Chan; Sargeant, Aaron M.; Yeh, Su-Peng; Liao, Yu-Min; Bai, Li-Yuan
Highlights Examine the impact of HCV infection on DLBCL patients receiving immunochemotherapy. 29 HCV-positive patients are compared with 139 HCV-negative patients. HCV infection results in more hepatic toxicity in DLBCL patients. HCV exaggerates hepatic toxicity and delays scheduled treatment. HCV infection does not affect 5-year PFS or 5-year OS.